SARS-CoV-2 anti-spike antibody titres after vaccination with BNT162b2 in naïve and previously infected individuals. Issue 8 (August 2021) - Lombardi, Andrea; Consonni, Dario; Oggioni, Massimo; Bono, Patrizia; Renteria, Sara U.; Piatti, Alessandra; Pesatori, Angela C.; Castaldi, Silvana; Muscatello, Antonio; Riboldi, Luciano; Ceriotti, Ferruccio; Bandera, Alessandra; et al.
Abstract: Great expectations are placed in vaccines against COVID-19 to control the pandemic. We reviewed the antibody titres in a cohort of healthcare workers (HCWs) vaccinated with BNT162b2 to assess the influence of a previous infection on them. We stratified the results according to the individual history of nasopharyngeal swab (NPS) and symptoms. Among 3475 HCWs the highest titres were recorded among those infected more than 6 months before vaccination, independently of symptoms, followed by those infected less than 6 months before vaccination, especially in those with symptoms, and by uninfected HCWs. Vaccination with BNT162b2 can boost immunity acquired through infection, particularly in those infected more than 6 months before vaccination.